The Roots of Informal Responses to Regulatory Change: Non‐compliant Small Firms and the National Living Wage. (2nd May 2019) - Ram, Monder; Edwards, Paul; Meardi, Guglielmo; Jones, Trevor; Doldor, Sabina
Abstract: How do small 'non‐compliant' firms (those evading existing regulations) react to further regulatory change? The impact of the National Living Wage in the UK in 2016 is analysed through 22 mostly longitudinal case studies of small non‐compliant firms. The varied responses, endurance of non‐compliance, and blurred and dynamic nature of transitions to compliance are discussed through the lens of institutional approaches to informality. The analysis sheds new light on the relative autonomy of micro processes and the conditions under which external forces affect these processes. Non‐compliant informality, as a persisting feature of small business, is unlikely to be transformed by legal regulation alone.